2020
DOI: 10.1093/texcom/tgaa051
|View full text |Cite
|
Sign up to set email alerts
|

Sharp Wave-Ripples in Human Amygdala and Their Coordination with Hippocampus during NREM Sleep

Abstract: Cooperative interactions between the amygdala and hippocampus are widely regarded as critical for overnight emotional processing of waking experiences, but direct support from the human brain for such a dialog is absent. Using overnight intracranial recordings in four pre-surgical epilepsy patients (three female), we discovered ripples within human amygdala during non-rapid eye movement (NREM) sleep, a brain state known to contribute to affective processing. Like hippocampal ripples, amygdala ripples are assoc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 73 publications
1
17
0
Order By: Relevance
“…Far less is known however about amygdala activity during SWS in humans. Recent research has shown that sharp-wave ripples occur in the human amygdala during SWS, and these are temporally linked with both ripples in the hippocampus and sleep spindles (though notably not slow oscillations) (Cox et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Far less is known however about amygdala activity during SWS in humans. Recent research has shown that sharp-wave ripples occur in the human amygdala during SWS, and these are temporally linked with both ripples in the hippocampus and sleep spindles (though notably not slow oscillations) (Cox et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Far less is known however about amygdala activity during SWS in humans. Recent research has shown that sharp-wave ripples occur in the human amygdala during SWS, and these are temporally linked with both ripples in the hippocampus and sleep spindles (though notably not slow oscillations) (Cox et al , 2020). This provides a potential physiological basis for emotional memory consolidation during SWS, although an association with memory is yet to be reported.…”
Section: Discussionmentioning
confidence: 99%
“…A key distinction between neutral and emotional memory formation is the involvement of the amygdala (Payne & Kensinger, 2018). While theories of memory consolidation highlight dialogue between the hippocampus and neocortex during SWS as being involved in memory consolidation, interactions between the hippocampus and amygdala, and their relevance for behavior, is currently underexplored (though see Cox et al, 2020). Furthermore, many studies examining SWS in relation to memory focus exclusively on sleep stage correlations.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, even the immobility-associated LRGN population in SO are heterogeneous, with some but not all cells showing activity that is phase-locked to sharp-wave ripples ( Katona et al, 2017 ; Francavilla et al, 2018 ). Interestingly, these HPC ripples are linked to memory consolidation in sleep ( Buzsaki, 2015 ; Oliva et al, 2020 ), potentially in coordination with cortical and subcortical regions ( Cox et al, 2020 ; Norimoto et al, 2020 ; Skelin et al, 2021 ). Thus, it is possible that HPC LRGNs may serve to synchronize activity in the HPC as well as in distributed brain regions in memory processing.…”
Section: Long-range Gabaergic Neurons In Brain Function and Physiolog...mentioning
confidence: 99%